The Preliminary Study of Effects of Tolfenamic Acid on Cell Proliferation, Cell Apoptosis, and Intracellular Collagen Deposition in Keloid Fibroblasts In Vitro - Dan Yi; Ji Bihl; Mackenzie S. Newman; Yanfang Chen; Richard Simman (Hindawi Limited, 2014)
Keloid scarring is a fibroproliferative disorder due to the accumulation of collagen type I. Tolfenamic acid (TA), a nonsteroidal anti-inflammatory drug, has been found to potentially affect the synthesis of collagen in rats. In this preliminary study, we aimed to test the effects of TA on cell proliferation, cell apoptosis, and the deposition of intracellular collagen in keloid fibroblasts. Normal fibroblasts (NFs) and keloid fibroblasts (KFs) were obtained from human dermis tissue. Within the dose range 10−3-10−6 M and exposure times 24 h, 48 h, and 72 h, we found that 0.55 × 10−3 M TA at 48 h exposure exhibited significantly decreased cell proliferation in both NFs and KFs. Under these experimental conditions, we demonstrated that (1) TA treatment induced a remarkable apoptotic rate in KFs compared to NFs; (2) TA treatment reduced collagen production in KFs versus NFs; (3) TA treatment decreased collagen type I expression in KFs comparing to that of NFs. In summary, our data suggest that TA decreases cell proliferation, induces cell apoptosis, and inhibits collagen accumulation in KFs.